A Study on Public Awareness Toward Recycling Activity in Mukim Bandar Segamat - Raja Hariz Najmi Bin Raja HairulNizam (Recent Trends in Civil Engineering and Built Environment, 2022)
People have created solid waste in daily life, which can intensify cause environmental issues. The practical method to decrease the municipal solid waste or Households Solid Waste (HSW) by the recycling practice. In order to accomplish reduce solid waste through recycling activity, people should understand the awareness of recycling practices behaviour. The objective of the study is to determine the relationship between the level of awareness of the public and recycling practices behaviour and identify the factor influence of waste separation among the Residences Mukim Bandar Segamat. The study area that been select are Taman Mida, Taman Perling, Taman Sri Pelangi and Taman Segar. This study used a questionnaire survey to collect data using two platform questionnaire form and online Google Form. Distributed to 200 respondents randomly in the study area which need to answer 4 sections. Data analyses that been use are Descriptive analysis, Regression and Correlation Analysis. The outcome shows that respondents have a good level of awareness about recycling activity and also know well the quality of their residential waste management. The Theory of Planned Behaviour (TPB) determinants show Perceived behavioural Control and Moral Norm have a significant relationship between the TPB component and Waste Separation Behaviour that influence respondents to waste separation and recycling. To enhance continuously increasing the awareness of recycling and waste separation government may able to stimulation the Separation at Source Initiative (SSI) legislation and implementation, focusing more on the intrinsical motivation of families member and communities.